PEMBENTUKAN KARAKTER ISLAMI PESERTA DIDIK MELALUI PROGRAM PEMBIASAAN KEAGAMAAN DI MADRASAH TSANAWIYAH MIFTAHUL ULUM KEROPAK - Intan fitriyani; Devy Habibi Muhammad; Khoirotun Nisail Fitriah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Islamic character education through religious activities at MTs Miftahul Ulum Keropak. The approach used is qualitative with a descriptive field research type. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The research informants consisted of the Principal, Islamic Religion Education Teachers, and Diniyah School Teachers selected using purposive sampling techniques. Data analysis used the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, as well as drawing and verifying conclusions. The research results show that the implementation of Islamic character education is carried out through various planned, routine, and continuous religious activities, including reading Surah Yasin together, performing Duha prayers in congregation, performing Zuhur prayers in congregation, holding istigasah every Friday, doing wirid together, giving charity and donations, celebrating Islamic holidays, as well as running diniyah school programs. The character values developed through these activities include religiosity, discipline, responsibility, leadership, honesty, social care, and politeness. Supporting factors for implementation include the commitment of the madrasa head, the active role of teachers as role models, foundation support, adequate facilities and infrastructure, a conducive madrasa environment, and parental support. Meanwhile, the inhibiting factors are low awareness among some students, the influence of the outside school environment, differences in family backgrounds, and limited time for program implementation. The implementation of religious activities has a positive impact on the development of students' character, reflected in increased awareness of worship, discipline, responsibility, leadership, social care, and politeness in daily life. This study contributes empirically by showing that the consistent integration of various religious habits can comprehensively shape students' Islamic character.